Biodegradable PASP can effectively inhibit nitrification, moderate NH3 emission, and promote crop yield. Issue 9 (29th July 2019) - Yang, Jinhui; Liu, Tai; Liu, Hongbin; Zhang, Dan; Zhai, Limei; Liu, Jian; Wang, Man; Chen, Yanxue; Chen, Bingyi; Wang, Hongyuan
ABSTRACT: Polyaspartic acid (PASP) is a low-cost, environmentally friendly, and multifunctional polymer material. The knowledge regarding the effects of PASPs, especially the PASPs with a different molecular weight (MW), on nitrogen use efficiency (NUE), ammonia (NH3 ) volatilization and nitrous oxide (N2 O) emission in crop fields is scarce. In this study, maize pot experiments were conducted to evaluate three types of PASPs with different MW. Five treatments were designed: (1) application of chemical phosphorus (P) and potassium (K) fertilizer (PK), (2) PK plus urea (NPK), (3) NPK plus PASP-1 (PASPT1, MW: 5517), (4) NPK plus PASP-2 (PASPT2, MW: 6934), and (5) NPK plus PASP-3 (PASPT3, MW: 7568). The yield indicators of crop height, straw dry weight and 100-grain weight showed that PASP application improved the crop growth. In PASP3, NUE reached 46.1%, almost double of that in NPK (28.6%). Moreover, there were significantly less N losses in the forms of NH3 volatilization and NO2 emission following PASP amendment than regular urea application. Another positive impact revealed that PASP inhibited the transformation of NH4 + -N to NO3 – N. Among the three PASPs, PASP-3 with the highest MW overall presented optimal effects, implying that MW was a major driving factor for PASP performance on maize production.